Systematic review and randomized controlled trial meta-analysis of the effects of physical activity interventions and their components on repetitive stereotyped behaviors in patients with autism spectrum disorder - Yang, Juanjuan; Li, Ruxin (Frontiers in Psychology, 2025)
ObjectiveTo systematically evaluate the effect of exercise intervention and its components on repetitive stereotyped behaviors in patients with autism spectrum disorder (ASD).MethodsA computer-based search was conducted in PubMed, Web of Science, The Cochrane Library, and EMbase databases for randomized controlled trials (RCTs) related to exercise interventions for repetitive stereotyped behaviors in patients with ASD. The search covered all available data from the inception of each database until January 2025. Meta-analysis was performed using RevMan 5.4 software, methodological quality was assessed using the ROB scale, and publication bias was evaluated using Stata 17.0 software.ResultsA total of 20 RCTs were included, comprising 671 patients with ASD. The meta-analysis results showed that exercise intervention had a positive effect on repetitive stereotyped behaviors in patients with ASD (SMD = −0.37, 95% CI: −0.52, −0.21, p < 0.05). Subgroup analysis results indicated that ball sports (SMD = −0.72, 95% CI: −1.09, −0.36, p < 0.001), longer duration (SMD = −0.55, 95% CI: −0.98, −0.12, p < 0.05), moderate to high frequency (SMD = −0.74, 95% CI: −1.05, −0.44, p < 0.001), longer time (SMD = −0.84, 95% CI: −1.26, −0.42, p < 0.001), and group participation (SMD = −0.48, 95% CI: −0.74, −0.21, p < 0.001) might show optimal dose–response relationships.ConclusionExercise intervention can effectively improve repetitive stereotyped behaviors in patients with ASD. The components of exercise intervention show a dose–response effect, with the best results likely occurring from ball sports, medium to long durations, moderate to high frequency, longer time, and group participation.Systematic review registrationThe protocol for this meta-analysis has been registered in INPLASY, with the registration number INPLASY202520074.